Phosphodiesterase 5 inhibitors for pulmonary hypertension - Barnes, Hayley (Cochrane Database Syst Rev, 2019)
BACKGROUND: Pulmonary hypertension (PH) comprises a group of complex and heterogenous conditions, characterised by elevated pulmonary artery pressure, and which left untreated leads to right‐heart failure and death. PH includes World Health Organisation (WHO) Group 1 pulmonary arterial hypertension (PAH); Group 2 consists of PH due to left‐heart disease (PH‐LHD); Group 3 comprises PH as a result of lung diseases or hypoxia, or both; Group 4 includes PH due to chronic thromboembolic occlusion of pulmonary vasculature (CTEPH), and Group 5 consists of cases of PH due to unclear and/or multifactorial mechanisms including haematological, systemic, or metabolic disorders. Phosphodiesterase type 5 (PDE5) inhibitors increase vasodilation and inhibit proliferation. OBJECTIVES: To determine the efficacy of PDE5 inhibitors for pulmonary hypertension in adults and children. SEARCH METHODS: We performed searches of CENTRAL, MEDLINE, Embase, CINAHL, and Web of Science up to 26 September 2018. We handsearched review articles, clinical trial registries, and reference lists of retrieved articles. SELECTION CRITERIA: We included randomised controlled trials that compared any PDE5 inhibitor versus placebo, or any other PAH disease‐specific therapies, for at least 12 weeks. We include separate analyses for each PH group. DATA COLLECTION AND ANALYSIS: We imported studies identified by the search into a reference manager database. We retrieved the full‐text versions of relevant studies, and two review authors independently extracted data. Primary outcomes were: change in WHO functional class, six‐minute walk distance (6MWD), and mortality. Secondary outcomes were haemodynamic parameters, quality of life/health status, dyspnoea, clinical worsening (hospitalisation/intervention), and adverse events. When appropriate, we performed meta‐analyses and subgroup analyses by severity of lung function, connective tissue disease diagnosis, and radiological pattern of fibrosis. We assessed the evidence using the GRADE approach and created 'Summary of findings' tables. MAIN RESULTS: We included 36 studies with 2999 participants (with pulmonary hypertension from all causes) in the final review. Trials were conducted for 14 weeks on average, with some as long as 12 months. Two trials specifically included children. Nineteen trials included group 1 PAH participants. PAH participants treated with PDE5 inhibitors were more likely to improve their WHO functional class (odds ratio (OR) 8.59, 95% confidence interval (CI) 3.95 to 18.72; 4 trials, 282 participants), to walk 48 metres further in 6MWD (95% CI 40 to 56; 8 trials, 880 participants), and were 22% less likely to die over a mean duration of 14 weeks (95% CI 0.07 to 0.68; 8 trials, 1119 participants) compared to placebo (high‐certainty evidence). The number needed to treat to prevent one additional death was 32 participants. There was an increased risk of adverse events with PDE5 inhibitors, especially headache (OR 1.97, 95% CI 1.33 to 2.92; 5 trials, 848 participants), gastrointestinal upset (OR 1.63, 95% CI 1.07 to 2.48; 5 trials, 848 participants), flushing (OR 4.12, 95% CI 1.83 to 9.26; 3 trials, 748 participants), and muscle aches and joint pains (OR 2.52, 95% CI 1.59 to 3.99; 4 trials, 792 participants). Data comparing PDE5 inhibitors to placebo whilst on other PAH‐specific therapy were limited by the small number of included trials. Those PAH participants on PDE5 inhibitors plus combination therapy walked 19.66 metres further in six minutes (95% CI 9 to 30; 4 trials, 509 participants) compared to placebo (moderate‐certainty evidence). There were limited trials comparing PDE5 inhibitors directly with other PAH‐specific therapy (endothelin receptor antagonists (ERAs)). Those on PDE5 inhibitors walked 49 metres further than on ERAs (95% CI 4 to 95; 2 trials, 36 participants) (low‐certainty evidence). There was no evidence of a difference in WHO functional class or mortality across both treatments. Five trials compared PDE5 inhibitors to placebo in PH secondary to left‐heart disease (PH‐LHD). The quality of data were low due to imprecision and inconsistency across trials. In those with PH‐LHD there were reduced odds of an improvement in WHO functional class using PDE5 inhibitors compared to placebo (OR 0.53, 95% CI 0.32 to 0.87; 3 trials, 285 participants), and those using PDE5 inhibitors walked 34 metres further compared to placebo (95% CI 23 to 46; 3 trials, 284 participants). There was no evidence of a difference in mortality. Five trials compared PDE5 inhibitors to placebo in PH secondary to lung disease/hypoxia, mostly in COPD. Data were of low quality due to imprecision of effect and inconsistency across trials. There was a small improvement of 27 metres in 6MWD using PDE5 inhibitors compared to placebo in those with PH due to lung disease. There was no evidence of worsening hypoxia using PDE5 inhibitors, although data were limited. Three studies compared PDE5 inhibitors to placebo or other PAH‐specific therapy in chronic thromboembolic disease. There was no significant difference in any outcomes. Data quality was low due to imprecision of effect and heterogeneity across trials. AUTHORS' CONCLUSIONS: PDE5 inhibitors appear to have clear beneficial effects in group 1 PAH. Sildenafil, tadalafil and vardenafil are all efficacious in this clinical setting, and clinicians should consider the side‐effect profile for each individual when choosing which PDE5 inhibitor to prescribe. While there appears to be some benefit for the use of PDE5 inhibitors in PH‐left‐heart disease, it is not clear based on the mostly small, short‐term studies, which type of left‐heart disease stands to benefit. These data suggest possible harm in valvular heart disease. There is no clear benefit for PDE5 inhibitors in pulmonary hypertension secondary to lung disease or chronic thromboembolic disease. Further research is required into the mechanisms of pulmonary hypertension secondary to left‐heart disease, and cautious consideration of which subset of these patients may benefit from PDE5 inhibitors. Future trials in PH‐LHD should be sufficiently powered, with long‐term follow‐up, and should include invasive haemodynamic data, WHO functional class, six‐minute walk distance, and clinical worsening.